A youth collective in a borderline state and a silenced cooperative alternative: something is wrong - Gallego Sánchez, Antonio (REVESCO. Revista de Estudios Cooperativos, 2023)
Not all decent possibilities of employment are visible, accessible and available to those who need to satisfy their lack of employability, which is the reason why this study proposes to contribute to understanding and building, from a broad perspective and logic, the causes and reasons (structure of obstacles) that explain the lack of visibility of cooperative entrepreneurship as a solid, validated and institutionally supported employability solution to the problem of youth unemployment.